Persepsi Nelayan Terhadap Status Konservasi Hiu dan Pengaruhnya Terhadap Penangkapan Hiu: Studi Kasus di Kabupaten Badung, Provinsi Bali - Eriq Imanuel; I Gede Hendrawan; Ni Luh Putu Ria Puspitha (Journal of Marine and Aquatic Sciences, 2018)
Shark is one of top predator that can define and control marine food chain. Shark breeding process is relatively slow and increase of catching activity has even given worse impact to shark population. Several endangered shark species has already protected the catch activity was banned. Some of them, such as Alopias superciliosus are found in Benoa and Kedonganan harbour. This condition happened because of not enough information and knowledge transfer to the local community about the protected species and catching regulation. Based on that information,the research about fishermen perception on shark conservation status and its correlation with the shark catch is important to be conducted. Data was collected using quisioner through interview approach. All the respondent is men with the age ranged from 16-67 years old, and 98% of respondent is labor. About 55% of the respondent graduated from elementary school. The result showed that the fisherman perception of shark conservation status categorized as good, while shark catch that is related with conservation in Badung district is categorized very good. The correlation of fisherman perception to shark conservation status with shark catching effort is negative, and significant to the shark catching effort (?=0,05) in Badung district. It means that if the fisherman perception to the shark conservation status in Badung district increased, so that the catch effort will be decrease.